PENINGKATAN EFISIENSI BIAYA PRODUKSI DENGAN METODE ACTIVITY BASED MANAGEMENT DI PT. XYZ - Dyah Mahastuti; Nazaruddin M; Anizar M. Kes (Departemen Teknik Industri Universitas Sumatera Utara, 2013)
PT. XYZ engaged in manufacture of spoon and fork with the kind of reservation make to stock. Price of spoon and fork on a PT. XYZ is more expensive than the production results of the spoon and fork Country China. It is caused due to the high production costs caused by the presence of waste activities. A study conducted in PT. XYZ aims at getting a low production cost (low cost production). To realize those goals companies must conduct an analysis of the activity of production to redesign activities by eliminating activities that do not add value thus lowering production costs. No value-added activity at PT. XYZ is the activity the transfer of materials. Activity Based Management (ABM) is a comprehensive and integrated approach that makes management attention was centred on activities conducted with the purpose of improving customer value and profits gained because it gives that value. ABM insists on controlling the activity through activity analysis. Results of the draft to improve the system by using the system of waging Merit Pay generating wage assignment without changing the wage standard has been set. For the results of the draft material transfer activity done by shortening the distance between the actual conditions of the machine of 251.91 m to 155.87 m and set a shorter transfer lines. By applying the results of the design will be achieved efficiency reduction production costs amounted to 0.23%